Reaction of lettuce genotypes to Lettuce mosaic virus-Most (LMV-Most) and characterization of the translation factor eIF4E - Moura, Monika Fecury [UNESP]; Silva, Norberto da [UNESP]; Motta Hoffmann, Maria Isabel [UNESP]; Pavan, Marcelo Agenor [UNESP]; Krause-Sakate, Renate [UNESP] (Empresa Brasil Pesq Agropec, 2018)
The objective of this work was to evaluate lettuce genotypes for their reaction to Lettuce mosaic virus (LMV; Most-type, isolate AF-199) and variations of the eukaryotic translation initiation factor eIF4E. All inoculated genotypes were susceptible to LMV, which was detected by RT-PCR using specific primer pairs. However, the accessions 169501, 169501C, 172918A, and 162499 showed late development of symptoms that appeared only on the inoculated leaves. Sequencing of the coding region of eIF4E showed that these genotypes have an eIF4E(0) (mol(0)) standard typical for their susceptibility to LMV, indicating that the phenotype found is not correlated to nucleotide variations in this translation factor.
Keywords: eIF4E; potyvirus; resistance